Asian discourses of rule of law : theories and implementation of rule of law in twelve Asian countries, France and the U.S. - Peerenboom, R. P. (Randall P.), 1958- (RoutledgeCurzon law in Asia., 2004)
Rule of law, one of the pillars of the modern world, has emerged in Western liberal democracies. This book considers how rule of law is viewed and implemented in the different cultural, economic and political context of Asia.